Student Perceptions: TikTok's vs. Movies' Role in Vocabulary Acquisition - Ain, Allysa Hurul; Kalisa, Pasca (Journal of English Language and Education, 2026)
Vocabulary is a fundamental component in English language learning, yet many students still struggle to enrich their vocabulary due to limited contextual learning in formal instruction. With the rise of digital platforms, TikTok and movies have become popular sources of authentic language input, though their effectiveness has rarely been compared directly. This study investigates students’ perceptions of TikTok and movies in vocabulary acquisition. Employing a qualitative case study, data were collected from 25 eleventh-grade students at MAN 1 Kabupaten Semarang through questionnaires combining Likert-scale items and open-ended questions. Findings reveal that while TikTok offers short, engaging, and easily accessible content, its effectiveness is often hindered by distractions and lack of contextual depth. In contrast, movies provide richer vocabulary exposure, contextualized usage, and higher retention, leading students to perceive them as more effective for vocabulary learning. The study concludes that movies serve as a more reliable medium for enhancing vocabulary acquisition.